Desenvolvimento e caracterização de comprimidos orodispersíveis liofilizados contendo omeprazol péletes - Facco, Grasiela (2020)
Omeprazole is the most used drug in the treatment of peptic acid disorders and when administered orally should be released rapidly in the early portions of the intestine. The pellets are pharmaceutical forms widely studied to apply drug release in the intestine, being administered by the patient in the form of capsules and tablets. In order to innovate and improve administration, drug availability and treatment adherence, new oral technologies are being used, such as orodispersible tablets designed to dissolve contact with saliva in the oral cavity without water, being a lyophilization a more studied technique due to the offer of advantages from a lyophilized orodispersible tablet. After evaluating the physicochemical characteristics of omeprazole, the fluidized bed was coated with different pellets skin, obtaining high yield, sphericity and good application performance. For an orodispersible matrix created from lyophilization, a 50:50 concentration of gelatin and mannitol results in tablets that look good, uniform, durable, and disintegrate resistant to fast disintegrating forms. The dissolution profile of orodispersible omeprazole shows similarity to the reference medicine, thus confirming the positive results for the treatment of stomach disorders using a viable and efficient alternative.